Rancang Bangun DATA MANIA sebagai Multimedia Interaktif Data Keselamatan Bahan Kimia Berbasis Augmented Reality - Aruna Pradipta; Malik Aziz; Iqbal Aulia Fajri; Miftahul Khair (Universitas Negeri Padang, 2020)
The Design of this Interactive Multimedia is motivated by the increasing number of work accidents that occur in chemical laboratories due to students lack of knowledge of properties about the properties of chemicals and work safety in the laboratory. Based on data obtained from research conducted at the existing SMAN in Temanggung sub-district, it was concluded that the level of student knowledge regarding the aspects of chemicals and work safety in the laboratory was not evenly distributed. Methods in making this application include collecting literature, designing and developing applications, trials and publications. The results of making this application can be used for practician especially students in experiments in chemical laboratories. With this interactive multimedia the Chemical Safety Data based on Augmented Reality can provide convenience in obtaining chemical information and can reduce the risk of work accidents in the Chemistry Laboratory.